Active Mixing of Disparate Inks for Multimaterial 3D Printing. Issue 7 (12th April 2019) - Ortega, Jason M.; Golobic, Melody; Sain, John D.; Lenhardt, Jeremy M.; Wu, Amanda S.; Fisher, Scott E.; Perez Perez, Lemuel X.; Jaycox, Adam W.; Smay, James E.; Duoss, Eric B.; Wilson, Thomas S.
Abstract: 3D printing of multimaterial parts relies upon efficient mixing of the ink components and a rapid response to composition changes. However, at low Reynolds numbers and large Peclet numbers, mixing disparate viscosity and density inks poses a challenge. In this study, the performance of active micromixers for disparate non‐Newtonian inks is evaluated using both experiments and computational fluid dynamics simulations. The mixing efficiencies are compared with scaling relationships for active micromixers. Using detailed simulation results, multiple factors are identified that can impact the micromixer response time during a composition change. Lastly, an active micromixer is proposed and evaluated to efficiently mix arbitrary multimaterial ink compositions and produce fine composition gradients within printed parts. Abstract : Materials with unique macroscale properties are fabricated using multimaterial 3D printers with active micromixers. The micromixer performance is analyzed with both experiments and simulations, which are compared to theoretical predictions. An active micromixer is then proposed and evaluated for 3D printing disparate viscosity and density inks.